Self-Regulated Learning Strategies in Instrument Education - Sabahat ÖZMENTES (İnönü Üniversitesi Eğitim Fakültesi Dergisi)
Instrument practicing process is accepted to be the basic activity to develop skills ininstrument education. In this respect such topics as instrument practicing strategiesand awareness influence student’s performance. The use of self regulatory learningstrategies while practicing the instrument is important for the independent and effectivelearners. In this study, a semi-structured interview was made with the studentsattending the Conservatoires at Hacettepe and Dokuz Eylül Universities and EducationDepartments in Dokuz Eylül and Gazi Universities to explore their self regulatorystrategies in instrument practicing process. Findings of the study are discussed relatedwith the literature.